2015
DOI: 10.1016/j.celrep.2015.03.026
|View full text |Cite
|
Sign up to set email alerts
|

IKCa Channels Are a Critical Determinant of the Slow AHP in CA1 Pyramidal Neurons

Abstract: Control over the frequency and pattern of neuronal spike discharge depends on Ca2+-gated K+ channels that reduce cell excitability by hyperpolarizing the membrane potential. The Ca2+-dependent slow afterhyperpolarization (sAHP) is one of the most prominent inhibitory responses in the brain, with sAHP amplitude linked to a host of circuit and behavioral functions, yet the channel that underlies the sAHP has defied identification for decades. Here, we show that intermediate-conductance Ca2+-dependent K+ (IKCa) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(135 citation statements)
references
References 38 publications
(53 reference statements)
3
129
3
Order By: Relevance
“…A recent publication suggested that KCa3.1 might be involved in the slow afterhyperpolarization in hippocampal neurons. 31 However, if there is any similarity between the roles of the fast (KCa1.1 ¼ BK), medium (KCa2 ¼ SK) and slow afterhyperpolarization (KCa3.1 ¼ IK) in terms of neuroprotection, then it would be highly unlikely that KCa3.1 inhibition would be neuroprotective by inhibiting the sAHP. Typically, compounds that enhance the AHP are neuroprotective, while blockers rather have the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication suggested that KCa3.1 might be involved in the slow afterhyperpolarization in hippocampal neurons. 31 However, if there is any similarity between the roles of the fast (KCa1.1 ¼ BK), medium (KCa2 ¼ SK) and slow afterhyperpolarization (KCa3.1 ¼ IK) in terms of neuroprotection, then it would be highly unlikely that KCa3.1 inhibition would be neuroprotective by inhibiting the sAHP. Typically, compounds that enhance the AHP are neuroprotective, while blockers rather have the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
“…In all these tissues, K Ca 3.1 regulates Ca 2+ signaling and membrane potential. Although two recent studies indicated that K Ca 3.1 may be expressed in neurons and that it may contribute to the slow afterhyperpolarization that follows a burst of action potentials in neurons of the hippocampus (King et al, 2015;Turner et al, 2015), another study presented data that K Ca 3.1 does not contribute to this slow AHP (Wang et al, 2016). The potential role of the channel in neurons therefore currently remains unclear.…”
Section: The K Ca 2 Family-small Conductance Channels Regulated mentioning
confidence: 97%
“…However, the observed magnitude of TRAM-34-sensitive I K in undifferentiated cells was considerably higher than that in RA-differentiated cells. Thus, as NSC-34 cells continue to differentiate with RA, the resultant decrease in the amplitude of TRAM-34-sensitive I K due to the decreased activity of IK Ca channels may not only produce a progressive reduction of K + efflux and depolarize the cell but also may result in the suppression of after-hyperpolarizing potentials [11,14]. Such maintained membrane depolarization accompanied by an increase in neuronal excitability would be prepared to elicit voltage-gated Na + or Ca 2+ currents in response to depolarizing inputs, thereby inducing regenerative neuronal firing [13,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the modulators of functional IK Ca channels have been demonstrated to perturb the functional activities of central neurons including motor neurons [8][9][10][11][12][13]. More specifically, the activity of these channels increases as voltage-gated Ca 2+ channels are facilitated by overactivity or neuron recovery (e.g., motor neuron recovery) during spinal cord injuries [8][9][10][11]. K Ca 3.1 channels appear to be strongly linked to a phenotype of hyperactivity disorder, at least in mice [13].…”
Section: Introductionmentioning
confidence: 99%